Aging Induces Tissue‐Specific Changes in Cholesterol Metabolism in Rat Brain and Liver. Issue 11 (22nd September 2013) - Smiljanic, Kosara; Vanmierlo, Tim; Djordjevic, Aleksandra Mladenovic; Perovic, Milka; Loncarevic‐Vasiljkovic, Natasa; Tesic, Vesna; Rakic, Ljubisav; Ruzdijic, Sabera; Lutjohann, Dieter; Kanazir, Selma
Abstract: Disturbance of cholesterol homeostasis in the brain is coupled to age‐related brain dysfunction. In the present work, we studied the relationship between aging and cholesterol metabolism in two brain regions, the cortex and hippocampus, as well as in the sera and liver of 6‐, 12‐, 18‐ and 24‐month‐old male Wistar rats. Using gas chromatography‐mass spectrometry, we undertook a comparative analysis of the concentrations of cholesterol, its precursors and metabolites, as well as dietary‐derived phytosterols. During aging, the concentrations of the three cholesterol precursors examined (lanosterol, lathosterol and desmosterol) were unchanged in the cortex, except for desmosterol which decreased (44 %) in 18‐month‐old rats. In the hippocampus, aging was associated with a significant reduction in lanosterol and lathosterol concentrations at 24 months (28 and 25 %, respectively), as well as by a significant decrease of desmosterol concentration at 18 and 24 months (36 and 51 %, respectively). In contrast, in the liver we detected age‐induced increases in lanosterol and lathosterol concentrations, and no change in desmosterol concentration. The amounts of these sterols were lower than in the brain regions. In the cortex and hippocampus, desmosterol was the predominant cholesterol precursor. In the liver, lathosterol was the most abundant precursor. This ratio remained stable during aging. The most striking effect of aging observed in our study was a significant decrease in desmosterol concentration in the hippocampus which could reflect age‐related reduced synaptic plasticity, thus representing one of the detrimental effects of advanced age.